USING BUSINESS INTELLIGENCE SOLUTIONS FOR COMPANY PERFORMANCE MANAGEMENT - Luminita SERBANESCU; Marian TAICU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2015)
An adequate performance management needs monitoring and reporting tools that should allow for making correct decisions. Currently, multiple operations specific to the managerial process in an organization require using information systems able to meet the requirements of the time factor in making decisions, as well as the need to identify alternative decisions. Information technologies have evolved continuously and rapidly over the past few years. Business Intelligence is a strong tool in the hands of companies, which can improve organizational performance providing valuable information on all aspects of a business. The paper presents a few aspects concerning the use of QlikView as a Business Intelligence tool for company performance management.